2019
DOI: 10.11648/j.fem.20190501.11
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Multidrug-Resistance Gram-Negative Bacteria from Hospital Sewage in North East, Nigeria

Abstract: Antibiotic resistance is on the verge of becoming top killer globally if left unattended in few decades to come.Much focus has been on clinical use and misuse of antibiotics and non-therapeutic applications in agriculture are blamed for the emergence of resistance. However, the rising incident of environmental spread of antibiotic is a major public health concern. The purpose of this study is to investigate the occurrence of gram-negative bacteria from hospitals sewage and evaluate the multi-drug resistant pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…A study from another developing country, Nigeria, also reported that bacterial genera, E. coli, Klebsiella, Pseudomonas, and Shigella were the most frequently distributed isolates in wastewater [7]. On the other hand, the most frequent MAR bacteria found in this study were S. aureus (20%), E. coli (20%), Enterobacter spp.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…A study from another developing country, Nigeria, also reported that bacterial genera, E. coli, Klebsiella, Pseudomonas, and Shigella were the most frequently distributed isolates in wastewater [7]. On the other hand, the most frequent MAR bacteria found in this study were S. aureus (20%), E. coli (20%), Enterobacter spp.…”
Section: Resultssupporting
confidence: 53%
“…Hospitals are the source of ARB, but it has been reported that these are potentially passed down to the community by the colonized patient and through hospital waste disposal facilities, especially wastewater [6,7]. Several reports have been focused on that Gram-negative isolates are frequently recovered from hospital wastewater among all pathogens and showed multidrug resistance [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, Morganella morganii isolates from Sikkim did not show any resistance to chloramphenicol. Multidrug resistant Morganella morganii (5.59%) was reported from Nigerian hospital wastes ( Mustapha and Imir, 2019 ). Cephalosporin (0.50%) and ciprofloxacin (0.50%) resistant Morganella morganii were reported from a healthy community of Chandigarh, India (0.50%) ( Monica et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, such an environment can be a pool of bacteria and resistant genes [84]. Here, hospital sewage that is discharged from an area can allow exchange between different bacterial populations [85]. The study reported high multidrug-resistant Gram-negative bacteria with high multiple antibiotic-resistant indexes (MARI) in hospital wastewater in Nigeria [85].…”
Section: How Water Environment Contributes To Spread Of Resistancementioning
confidence: 99%
“…Here, hospital sewage that is discharged from an area can allow exchange between different bacterial populations [85]. The study reported high multidrug-resistant Gram-negative bacteria with high multiple antibiotic-resistant indexes (MARI) in hospital wastewater in Nigeria [85]. Furthermore, discharge from health institutions into larger water receiving bodies may lead to the further spread of antibiotic resistance [67].…”
Section: How Water Environment Contributes To Spread Of Resistancementioning
confidence: 99%